2021
DOI: 10.1007/s12012-021-09703-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cardiotoxic Effects of Remdesivir on Cardiovascular System: A Literature Review

Abstract: Corona disease 2019 (COVID-19) pandemic continues to spread around the world with no efficacious treatment. Intravenous remdesivir is the only authorized drug for treatment of COVID-19 disease under an Emergency Use Authorization. Remdesivir is a 1′-cyano-substituted adenosine nucleotide prodrug which inhibits viral RNA synthesis. This metabolite is an adenosine analog but with a significantly longer half-life than adenosine. Adenosine is a powerful vasodilator that can cause profound hypotension which is foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 20 publications
1
55
0
3
Order By: Relevance
“…Some Covid‐19 patients on remdesivir may exhibit sinus bradycardia, hypotension, T‐wave abnormalities, and a prolonged QT interval. It has been shown that remdesivir have some cardiotoxic and proarrhythmic effects pronouncedly occur in patients with cardiovascular disorders 10 . Remdesivir is structurally like adenosine but with a longer half‐life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Covid‐19 patients on remdesivir may exhibit sinus bradycardia, hypotension, T‐wave abnormalities, and a prolonged QT interval. It has been shown that remdesivir have some cardiotoxic and proarrhythmic effects pronouncedly occur in patients with cardiovascular disorders 10 . Remdesivir is structurally like adenosine but with a longer half‐life.…”
Section: Discussionmentioning
confidence: 99%
“…9 Regarding cardiovascular complications, sinus bradycardia, hypotension, T-wave abnormalities, atrial fibrillation (AF), and a prolonged QT interval are the most common AEs. 10 It has been shown that remdesivir is adequately tolerated but does not provide significant therapeutic effects in seriously COVID-19 patients. Furthermore, there is a lack of clinical evidence to evaluate the appearance of remdesivir AE and outcomes in men and women and different age groups.…”
mentioning
confidence: 99%
“…Among the most frequent side effects of remdesivir seem to appear anemia, gastrointestinal symptoms, hypertransaminasemia, cutaneous rashes, and kidney injury, other than constitutional local reactions such as infusion-related ones [ 95 ]. Notably, patients may also experience hypotension and cardiac conduction disturbances, as documented by electrocardiographic monitoring.…”
Section: Potential Impact Of Antivirals On the Cardiovascular System ...mentioning
confidence: 99%
“…Remdesivir can exert an impact on cardiac tissue by inducing electrocardiographic changes such as bradycardia, T-wave abnormalities, atrial fibrillation, and prolonged QT interval [ 95 ]. In addition, a few cases of cardiac arrest were demonstrated following remdesivir infusion.…”
Section: Potential Impact Of Antivirals On the Cardiovascular System ...mentioning
confidence: 99%
“…Importantly, Bartoletti et al do not mention the severe cardiac side effects associated with RDV use that are now increasingly reported in international pharmacovigilance databases, including cardiac arrest, bradycardia, and hypotension[ 3 , 4 ]. Multiple case reports of bradycardia and other electrocardiogram changes have been reported in the literature following RDV administration[ 5 , 6 ].Mechanisms of RDV-induced cardiotoxicity are not elucidated but might include alterations in the adenosine metabolism[ 5 ] and in vitro data suggest a significant impact of RDV on cell viability of human pluripotent stem cell cardiomyocytes[ 3 ]. The recommendation to use RDV in hospitalized COVID-19 patients should be performed after careful assessment of the benefit-risk balance which has clearly changed since the initial publication of the ACTT-1 trial.…”
mentioning
confidence: 99%